Peran Pendidikan Anak Usia Dini dalam Meningkatkan Children’s Well-Being - Sumiyati Sumiyati; Taopik Rahman; Risbon Sianturi (Ar-Raihanah: Jurnal Pendidikan Islam Anak Usia Dini, 2026)
Children’s well-being is a critical aspect of early development that influences lifelong outcomes. Early Childhood Education (ECE) plays a significant role in fostering children’s well-being through structured learning environments, supportive relationships, and developmentally appropriate practices. Early childhood education (ECE) is important in supporting children's holistic development, particularly in promoting children's wellbeing. This study aims to systematically review existing literature to examine how early childhood education contributes to enhancing children's wellbeing across physical, emotional, social, cognitive, and psychological domains. This research employs a systematic literature review method by analyzing peer-reviewed journal articles published between 2015 and 2025 obtained from academic databases such as Google Scholar, ERIC, and Scopus. Articles were selected using predefined inclusion and exclusion criteria to ensure relevance and research quality. The findings indicate that high-quality early childhood education significantly contributes to children's wellbeing through supportive teacher–child interactions, play-based learning environments, social engagement opportunities, and emotionally secure classroom climates. Early childhood education programs were found to enhance children's emotional regulation, social competence, learning readiness, self-confidence, and overall mental health. Furthermore, factors such as teacher competence, parental involvement, curriculum quality, and inclusive learning environments were identified as key determinants influencing wellbeing outcomes. This review highlights that early childhood education should not solely focus on academic preparation but must prioritize children's holistic wellbeing as a foundation for lifelong development. The importance of a holistic and inclusive approach in PAUD to support child well-being and identify gaps for future research. The study provides implications for educators, policymakers, and parents to strengthen wellbeing-oriented practices within early childhood education settings. Future research is recommended to explore longitudinal impacts of early childhood education on children's wellbeing across diverse cultural contexts